2018
DOI: 10.1038/s41424-018-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of MicroRNAs in Esophageal Carcinoma: A Meta-Analysis

Abstract: BackgroundNumerous articles have reported that abnormal expression levels of microRNAs (miRNAs) are related to the survival times of esophageal carcinoma (EC) patients, which contains esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC). Nevertheless, there has not been a comprehensive meta-analysis to assess the accurate prognostic value of miRNAs in EC.MethodsStudies published in English up to April 12, 2018 that evaluated the correlation of the expression levels of miRNAs with overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Accumulating evidence has suggested the association between miR-133a and poor overall survival (OS) of patients with solid cancer 67 , 68 . A meta-analysis revealed that high expression of miR-133a was related to better prognosis and ameliorated clinicopathological features in digestive system cancers 69 .…”
Section: Mir-133a In Cancer Prognosismentioning
confidence: 99%
“…Accumulating evidence has suggested the association between miR-133a and poor overall survival (OS) of patients with solid cancer 67 , 68 . A meta-analysis revealed that high expression of miR-133a was related to better prognosis and ameliorated clinicopathological features in digestive system cancers 69 .…”
Section: Mir-133a In Cancer Prognosismentioning
confidence: 99%
“…MicroRNAs (miRNAs), a group of small single-strand non-coding RNAs, can inhibit mRNA translation or induce mRNA degradation by specifically binding to the 3' untranslated region sequence of mRNA target, thus regulating post-transcriptional gene expression[7]. MiRNAs participate in the progression, proliferation, and metastasis of cancer cells in almost all human cancers including ESCC[8]. MiRNAs are expressed in peripheral blood and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with normal samples, 21 significant DEMs were identified. Among them, hsa-miR-147e [ 46 ], hsa-miR-181d [ 47 ], hsa-miR-214 [ 48 , 49 ], hsa-miR-612 [ 50 ], hsa-miR-133b [ 51 ], hsa-miR-143 [ 52 55 ], hsa-miR-100 [ 56 ], hsa-miR-126* [ 57 ], hsa-miR-145 [ 52 , 58 60 ], hsa-miR-15b [ 61 ] were all reported in EC. Most importantly, hsa-miR-496, hsa-miR-214, hsa-miR-15b were found to be correlated with patient survival.…”
Section: Discussionmentioning
confidence: 99%